Removal of GABAA receptor γ2 subunits from parvalbumin neurons causes wide-ranging behavioral alterations - Leppä, Elli; Linden, Anni-Maija; Vekovischeva, Olga Y.; Swinny, Jerome D.; Rantanen, Ville; Toppila, Esko; Höger, Harald; Sieghart, Werner; Wulff, Peer; Wisden, William; Korpi, Esa R. (PLOS ONE, 2011)
We investigated the behavioral significance of fast synaptic inhibition by αβγ2-type GABAA receptors on parvalbumin (Pv) cells. The GABAA receptor γ2 subunit gene was selectively inactivated in Pv-positive neurons by Cre/loxP recombination. The resulting Pv-Δγ2 mice were relatively healthy in the first postnatal weeks; but then as Cre started to be expressed, the mice progressively developed wide-ranging phenotypic alterations including low body weight, motor deficits and tremor, decreased anxiety levels, decreased pain sensitivity and deficient prepulse inhibition of the acoustic startle reflex and impaired spatial learning. Nevertheless, the deletion was not lethal, and mice did not show increased mortality even after one year. Autoradiography with t-butylbicyclophosphoro[35S]thionate suggested an increased amount of GABAA receptors with only α and β subunits in central nervous system regions that contained high levels of parvalbumin neurons. Using BAC-transgenesis, we reduced some of the Pv-Δγ2 phenotype by selectively re-expressing the wild-type γ2 subunit back into some Pv cells (reticular thalamic neurons and cerebellar Pv-positive neurons). This produced less severe impairments of motor skills and spatial learning compared with Pv-Δγ2 mice, but all other deficits remained. Our results reveal the widespread significance of fast GABAergic inhibition onto Pv-positive neurons for diverse behavioral modalities, such as motor coordination, sensorimotor integration, emotional behavior and nociception.
Im Titel ist das letzte "A" bei GABAA tiefgestellt
Gesehen am 16.08.2022